Virtual bolus for total body irradiation treated with helical tomotherapy. (8th November 2015) - Moliner, Gilles; Izar, Françoise; Ferrand, Régis; Bardies, Manuel; Ken, Soléakhéna; Simon, Luc
Abstract : Intensity‐modulated radiation therapy (IMRT) for total body irradiation (TBI) is practiced in several centers using the TomoTherapy System. In this context the planning target volume (PTV) is the entire body including the skin. A safety margin in the air surrounding the body should be added to take into account setup errors. But using inverse planning, over‐fluence peak could be generated in the skin region to insure dose homogeneity. This work proposes to study the performance of the use of a virtual bolus (VB). A VB is a material placed on the skin surface during planning, but absent for the real treatment. The optimal VB that compensates large setup errors without introducing a high‐dose increase or hot spots for small setup errors was determined. For two cylindrical phantoms, 20 VBs with different densities, thicknesses or designs were tested. Dose coverage of the PTV (V95%) in the presence of simulated setup errors was computed to assess the VB performance. A measure of the dose increase in the phantom center due to the absence of the VB during treatment was also achieved. Finally, the fluence peak at the phantom edge was measured in complete buildup conditions using a large phantom and a detector matrix. Using these VBs, simulated setup errors were compensated to a minimum value of 2.6 and 2.1 cm for small and large phantom, respectively (and only 1.2 and 1.7 cm with no VB). An optimal double‐layer VB was found with a density of 0.4 kg . m − 3 and a total thickness of 8 mm; an inner layer of 5 mm was declared as the target for the treatment planning system and an additional layer of 3 mm was added to avoid the over‐fluence peak. Using this VB, setup errors were compensated up to 2.9 cm. The dose increase was measured to be only + 1.5 % at the phantom center and over‐fluence peak was strongly decreased. PACS numbers: 87.53 Bn, 87.55 D‐, 87.55 de, 87.55 dk